2014
DOI: 10.1159/000357841
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of a Placental Infarction Hematoma Associated with Fetal Growth Restriction, Preeclampsia and Fetal Death: Clinicopathological Correlation

Abstract: The lesion termed ‘placental infarction hematoma' is associated with fetal death and adverse perinatal outcome. Such a lesion has been associated with a high risk of fetal death and abruption placentae. The fetal and placental hemodynamic changes associated with placental infarction hematoma have not been reported. This paper describes a case of early and severe growth restriction with preeclampsia, and progressive deterioration of the fetal and placental Doppler parameters in the presence of a placental infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 63 publications
1
11
0
1
Order By: Relevance
“…Similarly to others, we found no differences in fetal vascular malperfusion between the EOPE and the LOPE groups, 42 but fetal vascular malperfusion in combination with maternal vascular lesions may be more dominant in EOPE with FGR than in EOPE without FGR. 43 This analysis also confirmed that IVT (Figure 1(H)) were slightly but statistically significantly more common in PE which confirms the data from the literature on the increased frequency of IVT in pregnancies complicated by hypoxia-related conditions such as PE and FGR 4448 and maternal diabetes mellitus. 49,50 However, no significant differences were found between severe and mild PE.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly to others, we found no differences in fetal vascular malperfusion between the EOPE and the LOPE groups, 42 but fetal vascular malperfusion in combination with maternal vascular lesions may be more dominant in EOPE with FGR than in EOPE without FGR. 43 This analysis also confirmed that IVT (Figure 1(H)) were slightly but statistically significantly more common in PE which confirms the data from the literature on the increased frequency of IVT in pregnancies complicated by hypoxia-related conditions such as PE and FGR 4448 and maternal diabetes mellitus. 49,50 However, no significant differences were found between severe and mild PE.…”
Section: Discussionsupporting
confidence: 87%
“…The pathologic processes implicated in fetal death include: infection 6584 , placental abruption, 5, 37, 70, 8592 vascular lesions of the placenta, 28, 35, 93100 preeclampsia, 41, 101105 fetal growth restriction 9, 106114 , maternal anti-fetal rejection, 35, 115120 metabolic disorders, 121133 genetic disorders, 80, 131, 134137 umbilical cord accident, 97, 138145 trauma 146148 , and placental senescence 22 ; however, most of the 47,000 stillbirths reported from developed countries in 2015 149 were classified as unknown etiology. It is currently believed that the causes of fetal loss change with gestational age: chromosomal abnormalities 150153 and infection 75 are the most common causes during the first half of pregnancy, placental causes (abruption or vascular abnormalities) 154156 , and maternal anti-fetal rejection 118 become the most common causes after 26 weeks until term 14 , after which the etiology of in most cases, especially after 40 weeks, is unknown 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study we found that the histopathological evidence of maternal and fetal vascular malperfusion were significantly higher in the placental tissues of the cases in comparison to controls. The presence of VI and RPH are indicative of placental hypoperfusion and are common findings in placenta of pre-eclamptic pregnancies [ 7 ]. Microthrombi, fibrin deposition and occlusion of the placental spiral arteries can lead to placental infarcts.…”
Section: Discussionmentioning
confidence: 99%